The effect of autonomy training on student engagement in junior high school students - Susanti, Indah Nova; Yuspendi, Yuspendi; Megarini, Maria Yuni (Universitas Muhammadiyah Surakarta, 2020)
The Purpose of this study was determine the effect of Autonomy training on student of “X” junior high school in Bandung. The Sample of this study was 20 students who were classified as having low student engagement degrees were choosen used purposive sampling method. The Student Engagement instrument (SEI) adapted from theory J. Appleton, S. Christenson, D. Kim, dan A. Reschly (2017)is self-repot measure of cognitive and affective. Criterion Validity of this Instrument is 0.302- 0.877 and reliability is 0.747. Behavioral Engagement instrument adapted from theory J. Appleton, S. Christenson, D. Kim, dan A. Reschly (2017), with criterion validity is 0.317- 0.605 only for this research. The result showed there was an increase in the level of student engagement before and after training, statistical test show Asymp Sig 0.05 (N=-3.923) indicates the Hi is accepted, there is a difference in student engagement through autonomy training on student. The suggestion of this research is that student are expected to able to apply this training activity to daily life such as the method of making plans, goal and effort before the beginning of the school semester, So that they can be regular to make targets by themeselves and achieve them.